‘I felt like she owns me’: exploitation and uncertainty in the lives of labour trafficking victims in Ireland - Doyle, David M. (The British journal of criminology, 2019)
Although the law relating to ‘modern slavery’ has received increased attention in recent years, the perspectives of labour trafficking victims rarely feature in the literature. The article explores how this vulnerable group experiences the Irish anti-trafficking regime in practice. Drawing on 15 semi-structured interviews, it shows that victims of labour trafficking in Ireland receive minimal assistance from the State at every stage of the trafficking cycle, from prevention and identification to seeking redress for harms suffered. The lived experiences of the participants cut across the spheres of employment, criminal and immigration law, stretching well beyond the ‘silo’ of the anti-trafficking framework. The article concludes by suggesting that victims’ perspectives are an essential part of evidence-based policy responses to the multi-faceted phenomenon of severe labour exploitation, as well as a comprehensive analytical framework. It agrees that existing critiques of the anti-trafficking paradigm are well-founded, but argues that they should also take account of the practical benefits for individuals who are granted ‘victim of trafficking’ status.